PENGEMBANGAN MEDIA POSTER BERBASIS TEKA-TEKI BERGAMBAR PADA MATERI KOLOID DI SMAN 1 DARUL IMARAH - Nurbaity Julianti; Muhammad Nasir; Sri Winarni (Universitas Syiah Kuala, 2023)
This study aims to describe the feasibility of pictorial riddle-based poster learning media on colloidal material and describe the responses of teachers and students to pictorial riddle-based poster learning media on colloidal material. This research method uses RD with a 4-D model, namely, define, design, develop and disseminate. The research subjects were 16 students of class XII IPA 1, consisting of 9 men and 7 women. The instruments used in this study were media validity assessment sheets by experts, teacher responses questionnaire sheets and student responses questionnaire sheets. The results showed that the poster media got very good scores. The feasibility assessment obtained a percentage of 96.4% with a very decent category. The responses of teachers and students respectively obtained 100% and 92.4% in the very good category.Keyword: Learning Media, Poster, Pictorial Riddle, Colloid